The Communication Pattern of Community based Organization in Preventing and Caring of People Living with HIV/AIDS in Bali - Susanti, Santi; Kusmayadi, Ika Merdekawati (International Journal of Psychosocial Rehabilitation, 2019)
Bali is a region in Indonesia that has significantly contributed to spreading the HIV virus to workers in various sectors. The workers’ origins are from many areas in Indonesia, but East Java has the most significant contribution. Its data records are from two Community-Based Organizations (CBO), namely Yayasan Kesehatan Bali (YAKEBA) and Yayasan Kerti Praja (YKP) in Bali. This research focuses on describing the model communication of YAKEBA and YKP as the CBOs in handling HIV/AIDS in Bali. It aims to reveal the method of YAKEBA and YKP in identified and described HIV/AIDS cases, as well as the model communication of YAKEBA and YKP in preventing and caring for PLWHA. The result shows that YAKEBA and YKP are taking preventive and curative measures systematically in handling HIV/AIDS in Bali. The actions are conducted with two methods, which are a mobile visitation and snowball toward the hidden population or key population (communities). The CBOs in Bali are employing model interpersonal communication with face-to-face methods toward People Living with HIV (PLWH). Moreover, for the LGBT communities, the CBOs utilize social media. As for the public, they apply group communication to promote and educate people on HIV/AIDS